2020
DOI: 10.3390/ani10020221
|View full text |Cite
|
Sign up to set email alerts
|

Horses Failed to Learn from Humans by Observation

Abstract: Animals can acquire new behavior through both individual and social learning. Several studies have investigated horses’ ability to utilize inter-species (human demonstrator) social learning with conflicting results. In this study, we repeat a previous study, which found that horses had the ability to learn from observing humans performing an instrumental task, but we include a control for stimulus enhancement. One human demonstrator and thirty horses were included, and the horses were randomly assigned to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…This finding is in line with previous studies where horses were faced with different tasks (e.g. when trying to get hay from triple tier hay nests (46), solving an operant task: (37), and during locomotion (47)) and also expressed behavior indicative of frustration. Although we were not able to disentangle cause and effect with our setup, this increased frustration/arousal could have potentially led to a negative feedback loop that might hamper subject's performance in subsequent trials of the task.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with previous studies where horses were faced with different tasks (e.g. when trying to get hay from triple tier hay nests (46), solving an operant task: (37), and during locomotion (47)) and also expressed behavior indicative of frustration. Although we were not able to disentangle cause and effect with our setup, this increased frustration/arousal could have potentially led to a negative feedback loop that might hamper subject's performance in subsequent trials of the task.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that horses expressed both behavioral and physiological signs of frustration when they were not able to solve the presented displacement task. This finding is in line with previous studies where horses were faced with different tasks [e.g., when trying to get hay from triple tier hay nests (Ellis et al, 2015), solving an operant task: (Rørvang et al, 2020b), and during locomotion (Ödberg, 1973)] and also expressed behavior indicative of frustration. Adding to this, the behavioral frustration data was obtained by 1/0 sampling which means the true frequency of frustration behavior is likely much higher.…”
Section: Discussionsupporting
confidence: 91%
“…Success rate in target training was also noted as successful trials out of 10 trials total (as all horses accomplished at least 80% success rate in their first session i.e., 10 trials). For all tests; choice test, and visible and invisible displacement task, success rate (successful trials out of 10) was noted, and behavior potentially indicative of frustration (defined as; scraping or stamping the pen bedding, scratching body, head shaking, or pawing (from Rørvang et al, 2020a , b ) was also noted as 1/0 sampling during each trial (hence maximum 10 occurrences per horse per test).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to other domestic animals, like dogs (Miklósi and Soproni 2006 ), cats (Mäses and Wascher 2022 ), goats (Kaminski et al 2005 ; Nawroth et al 2020 ) and horses (Krueger et al 2011 ; Proops and McComb 2010 ), who have already been documented to learn from humans (dogs: e.g. Huber et al 2009 ; Miller et al 2009 ; cats: Fugazza et al 2021 ; goats: Nawroth et al 2016a ; horses: Bernauer et al 2020 ; Schuetz et al 2017 ; but see Rørvang et al 2020 ; Burla et al 2018 ), pigs have been found to pay attention to humans and can learn to follow human-given cues like pointing gestures (Bensoussan et al 2016 ; Nawroth et al 2013 , 2014 ; Nawroth et al 2016a , b ; but see Albiach-Serrano et al 2012 ; Gerencsér et al 2019 ), or object handling (shaking of a food container, Albiach-Serrano et al 2012 ), although with inconsistent results due to the large variation in the given cue types (distal/proximal, sustained/momentary), or the subjects’ ages and pre-experiences. Although learning from humans about object manipulation might be additionally difficult due to differing morphologies, pigs might be a likely candidate for possessing heterospecific learning capabilities; especially if social tolerance is a driving factor in observational learning in adult pigs.…”
Section: Introductionmentioning
confidence: 99%